Comparative Assessment of Growth in Pure and Crossbred Turkeys in a Humid Tropical Environment - Ilori, A.M.; Peters, S.O.; Ikeobi, C.O.N.; Bamgbose, A.M.; Isidahomen, C.E.; Ozoje, M.O. (International Journal of Poultry Science, 2010)
Three hundred poults consisting of 120 local, 120 local x exotic crossbred and 60 exotic poults were generated from matings between indigenous and exotic turkeys. Feed and water intake, body weight and other linear body measurements were evaluated on weekly basis. These were used to compare the performance of pure and crossbred turkeys raised under natural heat stress environment. Growth parameters studied were significantly affected by turkey genotype (p